KEMAMPUAN BAKTERI DARt EKOSISTEM AIR HITAM KALIMANTAN TENGAH DALAM MEROMBAK MINYAK BUMI DAN SOLAR - Iswandi Anas; Noegroho Hadi; Dwi Andreas Santosa (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 1999)
The objective of this experiment was to evaluate the abili!y of bacteria strains isolated from black water ecosystem of Central Kalimantan in degrading crude oil and diesel oil. The experiment was conducted at the Laboratory of Soil Biology, Department of Soil Sciences, Faculty of Agriculture, Bogor Agricultural University (IPB). The crude oil degrading ability of bacteria was tested on a minimum liquid medium (Gurujeyalakshmi dan Orial, 1989) and soil. Six crude oil and diesel oil degrading bacteria were isolated. The bacteria were identified as Bacillus panthotenticus (2 strains), B. circulars (1 strain), Pssudomonas diminuta (1 strain), P. stufzeri (1 strain) and Klebsiella edwardsii (1 strain). These bacteria were able to degrade crude oil or diesel oil whether in a liquid minimum medium or in soil.On a minimum liquid medium, after 10 days incubation, bacteria were able to degrade 20.49% of the crude oil, while in the Entisol soil, after 7 days of incubation, as high as 40.29% of crude oil was degraded and after 28 days incubation, 64.95 of crude oil had been degraded by selected bacteria.